Clinical Outcomes of Volumetric Modulated Arc Therapy Following Intracavitary/Interstitial Brachytherapy in Cervical Cancer: A Single Institution Retrospective Experience - Lin, Yanzhu; Ouyang, Yi; Chen, Kai; Lu, Zhiyuan; Liu, Yonghong; Cao, Xinping (Frontiers in Oncology, 2019)
Purpose: To evaluate treatment outcomes and toxicity in patients with cervical cancer (CC) treated with volumetric modulated arc therapy (VMAT), followed by three-dimensional high-dose-rate intracavity combined with interstitial brachytherapy (IC/IS BT) compared with intensity-modulated radiation therapy (IMRT) treatment. Materials and methods: A total of 398 patients with stage IA–IVB CC treated with definitive radiotherapy with or without chemotherapy were retrospectively analyzed (331 VMAT and 67 IMRT). A total prescription dose of 45–50 Gy was delivered to pelvic field with VMAT/IMRT in 25/28 fractions, with five fractions per week. Every patient further received IC/IS BT for four to six 6.0-Gy fractions. Local control (LC), disease-free survival (DFS), overall survival (OS), and distant metastasis-free survival (DMFS) rates were calculated. Acute hematotoxicity and late toxicity was recorded. Results: The median follow-up period was 25.47 (range, 0.93–58.93) months for the VMAT and 35.07 (4.8-90.37) months for IMRT. The 3-year OS, DFS, LC and DMFS rate were 80.5%, 65.4%, 88.7% and 78.1% in VMAT group, and 76.2%, 76.4%, 83.1% and 86.1% in the IMRT group, respectively. No significant differences were found between VMAT and IMRT groups for OS, DFS, LC and DMFS rate. However, patients in the VMAT group had lower incidences of chronic enterocolitis complications (26.6% vs. 38.8%, p=0.004). In addition, a total of 3 (0.9%) patients developed grade 3 chronic cystitis, and 7 (2.1%) patients developed grade 3 or greater chronic enterocolitis in VMAT group. Conclusion: VMAT combined with IC/IS BT can result in satisfactory curative outcomes and low incidences of late radiation enterocolitis and cystitis in CC treatment.